Production and characterization of a monoclonal antibody specific to the M serotype of plum pox potyvirus - Boscia, D.; Zeramdini, H.; Cambra, Mariano; Potere, O.; Gorris, María T.; Myrta, A.; DiTerlizzi, B.; Savino, V. (2017)
A monoclonal antibody to an Albanian isolate of plum pox potyvirus (PPV) was obtained (MAbAL), that specifically recognized strain M of this virus. The specificity of MAbAL, assessed by comparative ELISA on 130 PPV isolates of different geographical origin, 22 of which were also tested by comparative IC-PCR, gave consistent and highly reproducible results. MAbAL seems to be elicited by a stable surface determinant that makes it particularly suitable for successful use under a wide range of conditions. MAbAL is an useful addition to the panel of PPV-specific MAbs available to date.